2019
DOI: 10.12659/ajcr.918770
|View full text |Cite
|
Sign up to set email alerts
|

Complete Response of Chemo-Refractory Metastatic Metaplastic Breast Cancer to Paclitaxel-Immunotherapy Combination

Abstract: Objective: Rare disease Background: Metaplastic breast cancer (MPBC) is a rare subtype of breast cancer that is difficult to manage and is resistant to therapy. Immunotherapy is becoming a promising option for care of several types of cancers including triple negative breast cancer. Case Report: We present a case of a patient with chemo-refractory metastatic metaplastic-type of breast cancer with failures to 3 active lines of chemotherapy. The patient achieved a complete and sustained response to chemo-immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…17 Similarly, Al Sayed et al reported a complete response to the combination of a novel anti-PD-L1 antibody, durvalumab, with paclitaxel in a patient with chemoresistant, metastatic MBC whose neoplastic cells overexpressed PD-L1. 41 In our study, 2 PD-L1-positive (one in TC and IC, respectively) spindle cell carcinomas harbored PTEN mutations. PTEN mutations in cancer cells may induce immunosuppressive expression signatures and the lack of response to anti-PD-1 therapies.…”
Section: Semir Vranic Et Almentioning
confidence: 47%
“…17 Similarly, Al Sayed et al reported a complete response to the combination of a novel anti-PD-L1 antibody, durvalumab, with paclitaxel in a patient with chemoresistant, metastatic MBC whose neoplastic cells overexpressed PD-L1. 41 In our study, 2 PD-L1-positive (one in TC and IC, respectively) spindle cell carcinomas harbored PTEN mutations. PTEN mutations in cancer cells may induce immunosuppressive expression signatures and the lack of response to anti-PD-1 therapies.…”
Section: Semir Vranic Et Almentioning
confidence: 47%
“…Anecdotic observations have demonstrated that some MBC can respond to check-point inhibitors. Thus, Adams et al [ 81 ] and Al Sayed et al [ 82 ] reported complete responses to pembrolizumab and durvalumab, respectively, in two patients with advanced MBC with PD-L1 tumor cell expression. The DART study (NCT02834013) evaluates dual anti-CTLA-4 (ipilimumab) and anti-PD-1 (nivolumab) blockade in rare tumors, including an MBC cohort (Arm 36) [ 11 ].…”
Section: Targeted Therapy In Mbcmentioning
confidence: 99%
“… 46 A similar combination of durvalumab (anti-PD-L1) and paclitaxel was also shown to provide a sustained, complete response in a second case report of advanced MpBC, this time with squamous features. 47 In this case, 20% of tumor cells stained with medium intensity (clone SP142), and there was an absence of staining in the TILS; while in the former case, 100% of tumor cells stained positively for PD-L1 using the 22C3 clone. Indeed, there is no standardized definition criteria for PD-L1 staining at this stage, and the characterization of expression of this and other immune checkpoint markers across TNBC and MpBC has only recently emerged.…”
Section: Precision Oncology For Mpbcmentioning
confidence: 67%